Continental Break‐Up Under a Convergent Setting: Insights From P Wave Radial Anisotropy Tomography of the Woodlark Rift in Papua New Guinea. Issue 5 (9th March 2022) - Yu, Youqiang; Tilmann, Frederik; Zhao, Dapeng; Gao, Stephen S.; Liu, Kelly H.
Abstract: To explore the dynamic mechanism of continental rifting within a convergent setting, we determine the first P wave radial anisotropic tomography beneath the Woodlark rift in southeastern Papua New Guinea, which develops within the obliquely colliding zone between the Australian and southwest Pacific plates. The rift zone is depicted as localized low‐velocity anomalies with positive radial anisotropy, which rules out a dominant role of active mantle upwelling in promoting the rift development and favors passive rifting with decompression melting as main processes. Downwelling slab relics in the upper mantle bounding the rift zone are revealed based on observed high‐velocity anomalies and negative radial anisotropy, which may contribute to the ultra‐high pressure rock exhumations and rift initiation. Our observations thus indicate that the Woodlark rift follows a passive model and is mainly driven by slab pull from the northward subduction of the Solomon plate. Plain Language Summary: The Woodlark rift in Papua New Guinea develops within the shear zone between the Australian and southwest Pacific plates and is one of the youngest and most rapidly extending continental rifts in the world. In this work, we analyze teleseismic P wave arrivals to study both 3‐D velocity and radial anisotropy structures of the upper mantle, offering new evidence to understand rift initiation under a generally convergent setting. Slab remnants in the upper mantle bordering the rift zone are detected and sinking into the deeper mantle. Downwelling of these slab segments may induce small scale return flows in the mantle and contribute to exhumation of the ultra‐high pressure rocks and rift development. Significant low‐velocity anomalies are revealed beneath the rift zone and have consistently positive radial anisotropy, which indicates a dominant strain in the horizontal plane and supports a passive rifting model, where mantle material is brought to shallower depths simply as a result of the extension of the lithosphere and melt is produced due to the lowered melting point at reduced pressure (decompression melting). Tensional stresses transferred from slab pull of the northward Solomon subduction are probably driving the rifting. Key Points: P wave radial anisotropic structure beneath the young and highly extended Woodlark rift is constrained from teleseismic tomography Downwelling of slab relics bordering the rift zone may contribute to ultra‐high pressure rock exhumation and rift development Slab‐pull drives rift initiation and induces decompression melting in the upper mantle under the rift zone by horizontal stress transfer